Endocrine disruption and commensal bacteria alteration associated with gaseous and soil PAH contamination among daycare children. (September 2019) - Roslund, Marja I.; Rantala, Sonja; Oikarinen, Sami; Puhakka, Riikka; Hui, Nan; Parajuli, Anirudra; Laitinen, Olli H.; Hyöty, Heikki; Rantalainen, Anna-Lea; Sinkkonen, Aki; ,
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are priority environmental pollutants that cause adverse health effects. PAHs belong to endocrine signaling disruptors to which children are sensitive to. Recent evidence suggests that PAH pollution alters the abundance of environmental bacteria that is associated with health outcomes. The alteration of environmental and commensal microbiota by PAH pollution has never been connected to endocrine signaling pathways. To estimate the risk of endocrine disruption in daycare children, we measured PAHs from soil and air of eleven urban daycare centres in Finland. We analyzed daycare yards' soil and children's gut and skin bacterial communities with 16S rRNA gene metabarcoding and used Kyoto Encyclopaedia of Genes and Genomes database to categorize endocrine signaling pathways. We also assessed the PAH hazard to children's health based on the current risk assesments. We observed associations between signaling pathways in endocrine system and gaseous PAH levels in ambient air. Peroxisome proliferator-activated receptor and adipocytokine signaling pathway decreased with higher chrysene concentration in the air. Soil PAH contamination was associated with altered Actinobacteria, Bacteoridetes and Proteobacteria communities on children's skin and in daycare yard soil. However, adjusted genera were not the same in soil and on skin, with the exception of Mycobacterium that was associated with higher PAH concentrations both in soil and on the skin. Even though fluoranhtene levels were above the current threshold values, total PAHs were below safety threshold values and based on current risk assessments there is a minor risk for child health. Our findings indicate that PAH concentrations that are considered safe may interfere with endocrine signaling by commensal microbiota and alter both environmental and commensal bacterial communities. The imbalance in human microbiota and the decrease in signaling pathways may contribute to emerging public health problems, including inflammatory disorders, obesity and diabetes. Therefore, the optimal risk assessments of PAHs and theoretically also other contaminants shaping commensal microbiota may need to take into account the possibility of the disruption of endocrine signaling pathways. Highlights: Gaseous PAHs in ambient air may disrupt endocrine signaling pathways in children. PAHs found from the living environment may alter both environmental and commensal bacterial communities. Current risk assessments may underestimate the hazard of PAHs.